Catalytic asymmetric total syntheses of myrtucommuacetalone, myrtucommuacetalone B, and callistrilones A, C, D and E. Issue 6 (11th December 2017) - Cheng, Min-Jing; Cao, Jia-Qing; Yang, Xin-Yi; Zhong, Li-Ping; Hu, Li-Jun; Lu, Xi; Hou, Bao-Long; Hu, Ya-Jian; Wang, Ying; You, Xue-Fu; Wang, Lei; Ye, Wen-Cai; et al.
Abstract : A highly concise catalytic approach for the first asymmetric total syntheses of myrtucommuacetalones and callistrilones is reported. Abstract : Herein, we describe a concise catalytic approach to the first asymmetric total syntheses of myrtucommuacetalone, myrtucommuacetalone B, and callistrilones A, C, D and E. The syntheses proceed in only 5–7 steps from the readily available compound11, without the need for protecting groups. Key features of the syntheses include a unique organocatalytic asymmetric Friedel–Crafts-type Michael addition with high enantioselectivity and a broad substrate scope, a novel Michael-ketalization-annulation cascade reaction, and an oxidative [3 + 2] cycloaddition. Furthermore, the new compound7 exhibited potent antibacterial activities against several multidrug-resistant strains (MRSA, VISA and VRE), and showed greater potency than vancomycin.